The impact of bacterial exposure in early life on lung surfactant gene expression, function and respiratory rate in germ-free mice - Barfod, Kenneth Klingenberg; Lui, Julian Chun; Hansen, Signe Schmidt Kjølner; Sengupta, Sreyoshee; Zachariassen, Line Sidsel Fisker; Hansen, Axel Kornerup; Sørli, Jorid Birkelund (Frontiers in Microbiomes, 2023)
Early life changes to lung and gut microbiota have been linked to alterations in immune responses, which may lead to pulmonary diseases later in life. Associations between early-life microbiota, germ-free status, lung gene expression, lung development and function are not well described. In this study, we compare early-life lung gene transcription under germ-free and different perinatal microbial exposures and analyze with a predetermined focus on lung capacity and lung surfactant. We also analyze the later-in-life physiological measures of breathing patterns and lung surfactant function between the germ-free, gnoto-phoric and gnoto-biotic offspring. To achieve this we kept pregnant BALB/c germ-free mice in separate germ-free isolators until exposure to either A: no exposure (GF), B: Bifidobacterium animalis ssp. Lactis (BI04) or C: full cecum content harvested from other female SPF mice (Cecum). Subsequently, perinatally exposed offspring were used for the analyses. Lung tissue transcriptomics analysis was done at postnatal day 10 (PNday10) at first phase of lung alveolar development. Head-out plethysmography for breathing pattern analysis was performed on the siblings at PNday23 followed by lung surfactant collection. The function of the collected lung surfactant was then analyzed ex vivo using the constrained drop surfactometer. Our results show, that lung transcriptomics had differentially expressed genes related to surfactant turnover between groups and sex at PNday10. We also show that the GF and BI04 animals had lower respiratory rate than Cecum mice, or compared to age matched specific pathogen free (SPF) reference animals. We also see changes in lung surfactant function ex vivo. The overall conclusions are that 10-day old GF mice do not have a markedly different lung gene transcription compared to gnoto-phoric or gnoto-biotic mice, but genes related to surfactant metabolism are among the few differentially expressed genes. We show here for the first time that early-life microbiome status correlates with early-life surfactant gene-transcription and to later-in-life lung surfactant function and associated respiratory rate changes in mice.